2022
DOI: 10.3390/clockssleep4010011
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Sex, Snoring and Severity of OSA in a First Nation Community in Saskatchewan, Canada

Abstract: Sleep disorders have been related to body weight, social conditions, and a number of comorbidities. These include high blood pressure and type 2 diabetes, both of which are prevalent in the First Nations communities. We explored relationships between obstructive sleep apnea (OSA) and risk factors including social, environmental, and individual circumstances. An interviewer-administered survey was conducted with adult participants in 2018–2019 in a First Nations community in Saskatchewan, Canada. The survey col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The baseline survey of the First Nations Sleep Health Project (FNSHP) was completed between 2018 and 2019 in collaboration with the two Cree First Nations (Community A and Community B) in Saskatchewan, Canada. The methods were published elsewhere [ 64 , 65 , 66 ] and are only briefly described here. The overall goal of the FNSHP was to study the relationships between sleep disorders, risk factors, and co-morbidities and to evaluate local diagnosis and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline survey of the First Nations Sleep Health Project (FNSHP) was completed between 2018 and 2019 in collaboration with the two Cree First Nations (Community A and Community B) in Saskatchewan, Canada. The methods were published elsewhere [ 64 , 65 , 66 ] and are only briefly described here. The overall goal of the FNSHP was to study the relationships between sleep disorders, risk factors, and co-morbidities and to evaluate local diagnosis and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline survey of the First Nations Sleep Health Project (FNSHP) was completed between 2018 and 2019 in collaboration with two Cree First Nation communities (Community A and Community B) in Saskatchewan, Canada. The methods were presented elsewhere [ 16 , 17 , 18 ] and are briefly described here. The overall goal of the FNSHP was to study the relationships between sleep disorders, risk factors and co-morbidities, and to evaluate local diagnosis and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent studies from the Top End, NT of Australia have reported that Aboriginal Australians demonstrate a higher overall severity of OSA, in the presence of concurrent medical comorbidities, such as hypertension, cardiovascular disease, chronic renal disease, and diabetes [ 23 , 24 ]. From a global perspective, there are only a small number of studies that have investigated OSA among First Nations Indigenous peoples [ 25 , 26 ]. However, studies from the New Zealand First Nations Māori have demonstrated a higher proportion of poor sleep quality and higher levels of OSA [ 27–29 ].…”
Section: Introductionmentioning
confidence: 99%